Coverage, social mobilization and challenges of mass Zithromax administration campaign in South and South East zones of Tigray, Northern Ethiopia: A cross sectional study. - Afework Mulugeta; Gebremedhin Berhe Gebregergs; Selamawit Asfaw; Dejen Yemane; Mengistu Mitiku; Beyene Meresa; Goitom Gigar; Amanuel Kidane (Public Library of Science (PLoS), 2018)
The antibiotic treatment of people with trachoma helps to prevent transmission the disease in a community. Currently, Zithromax is the drug recommended for mass drug administration (MDA). MDA should be carried out annually for three to five years in trachoma endemic areas. Coverage survey is essential to track progress towards program goals and to identify communities with poor coverage in order to permit timely and appropriate actions. We assessed mass Zithromax administration coverage, social mobilization and campaign challenges in south and southeast zones of Tigray, Ethiopia.We conducted a survey in community in Southern and South East zones of Tigray region from August 15 to August 31, 2016. The survey included nine Woredas. It was supported by qualitative methods. A total of 3741 individuals were enrolled from 933 households using multistage sampling. We used structured questionnaire. In-depth interview and focus group discussion were also applied. Descriptive statistics was performed using SPSS version 20.We thematically analyzed the qualitative data using Atlas 7.The overall coverage of Zithromax MDA was 93.3%. It ranges from 90.0% in Seharti Samre to 97.9% in Endamokoni. The coverage was 93.4% for males and 93.1% for females. A higher proportion (98.3%) of children aged 5 to 15 years and 409 (87.8%) under five children took Zithromax. The coverage was 94% in rural and 91.2% in urban. Women development army (43.3%) and health extension workers (32.5%) were the main source of information. Frequent occurrence of drug side effects, rumors, lack of community and leaders' engagement in the campaign, fasting, shortage of human power and short term unavailability of supplies were barriers during the campaign.The Zithromax MDA coverage in the study zones was higher than the minimum WHO set criteria of 80%. There was a wide difference in coverage among Woredas and Kebeles. The MDA coverage was lower in urban than rural. Misconceptions and poor mobilization were common challenges. Thus, proper planning, community mobilization and uniform training will need to be done ahead of the campaign in the future.